NSW Port Macquarie Penal Settlement (1821-1826) - Finnane, Mark (ADA Dataverse, 2021)
This data is a record of the population of convicts at the Port Macquarie Penal Settlement, 1821-1832, collated by David Roberts and Melissa Gibbs (University of New England) from records in the NSW State Archives, including 'Gaolers Lists' and a 'Port Macquarie Population Book'. These were prisoners sentenced to forms of secondary transportation in NSW, for the most part following their earlier transportation as penal convicts from Britain and Ireland. The data includes names, date of trial, sentence to be served at Port Macquarie.